Rohdea grandiflora (Asparagaceae), a new species from southern Gansu, China - Feng, Hui Zhe; Yu, Miao; Fang, Hong Lin; Han, Qing Xiang (Phytotaxa, 2022)
Rohdea grandiflora, a new species from Gansu, China, is described and illustrated. It is most similar to R. pachynema in sharing a long slender subterranean stolon, but differs mainly by the longer inner bracts, larger flowers, and columnar filaments adnate to the middle or basal portion of perianth lobes and not connate to adjacent ones.